Framing of Pulwama Attack in English Press: An Analysis from Pakistan in Context of Indo-Pak Conflict - Shahzad, Faisal; Kiran Tauseef; Usman Sadiq (Journal of Peace, Development and Communication, 2024)
The Pulwama attack on February 14, 2019 in the Indian administered Kashmir, worsened the Indo-Pak bilateral relation and brought both the nuclear states on the verge of war. In the ever growing and unending hostility between these rival states, the role of media is worth discussion as it plays important role in constructing war, peace, ideologies, and dissemination of these frames. This research employed the framing theory of Erving Goffman (1974) and discourse analysis coupled with Entman (1993) model of framing-as functionalized in the studies of Papacharissi& Oliveira, (2008); Semetko&Valkenburg, (2000) to examine the coverage of Pulwama attack in Kashmir in Dawn and The News newspapers, one of the leading English language dailies in Pakistan. This study analyzedthe editorials of elite English press of India and Pakistan regarding the Pulwama attack and the unrest created due to this terror attack. The study critically analyzed the mediatedthemes to reveal the dominant frames used by elite newspapers of Pakistan vis-à-vis the Kashmir conflict. The findings unveil that both the selected newspapers namely Dawn and The News used different frames and themes to conceptualize the Pulwama attack. Both the newspapers carried the elite oriented approach as well as bilateral cum human rights issue having repercussions for regional peace. The study concludes that the elite press reproduced and reinforced the dominant narratives and closely followed the foreign policy discourse of their respective countries. The study found that both Dawn and The News were dominated by the theme of Kashmir cause and episodic frames and less focus was given to Pakistan’s stance on Kashmir and the thematic frame during the conflict of Pulwama terror attack.